Van der Woude Syndrome: Presentation of Two Cases - Köse, Rüştü; Tuna, A. Burçe Karantinaci (Fırat University, 2012)
Van der Woude Syndrome is a rare genetic disorder inherited in an autosomal dominant pattern. It is the most common syndrome that accompanies cleft lip and/or palate. The most common expression of the disease is symmetrical, volcanic crater-like pitting or mounding in the lower lip vermilion. For the treatment of lower lip sinuses, simple elliptical excision is the most commonly employed technique. Although this technique is simple and easy to perform, recurrence of the sinuses and loss of lip tone are common after surgery. The clinical manifestations of this syndrome are usually treated without due consideration to the underlying cause. Often this results in misdiagnosis of the other associated abnormalities of the syndrome like sub-mucous cleft palate. We discuss two cases in this paper. One of the patients underwent corrective cleft palate surgery without a requisite comple-mentary lower lip sinus excision due to parental objection, and the other with surgically treated lower lip sinuses.

Genetik ve otozomal dominant olan Van der Woude Sendromu, yarık dudak-damak ile birliktelik gösteren en sık sendromdur. En sık görülen şekli alt dudak vermilyonunda, orta hattın her iki yanında simetrik volkan krateri görünümünde sinüslerin olmasıdır. Alt dudak sinüslerinin tedavisinde basit eliptik eksizyon en sık kullanılan tekniktir. Basit olmasına rağmen bu teknik her zaman sinüs tekrarı ve dudakta tonus kaybı gibi problemleri tam olarak çözmemektedir. Bu sendrom çoğu zaman akla gelmemekte ve teşhis konmadan tedavi edilmektedir. Bu durum hastalarda mevcut olabilecek submuköz yarıkların tedavi edilmeden kalmasına ve başka organ anomalilerinin araştırılmamasına sebep olmaktadır. Biz bu yazıda dudaktaki sinüsler için tedavi istenmeyen yalnızca damak yarığı onarım ameliyatı yapılmış bir hasta ve dudaktaki sinüsleri tedavi edilmiş bir başka vaka olmak üzere iki olguyu tartıştık.
Van der Woude Sendromu: 2 Olgu Sunumu